Implementation of Business Services Retribution Policy in Tomohon City (Study on Optimizing Retribution for Tourism Areas in Tomohon City) - Victory Hendry Bogia (Syntax Corporation Indonesia, 2021)
This study aims to analyze and explain the implementation of business service retribution policies in Tomohon City, this study uses a qualitative descriptive method. Data collection techniques with interviews and documentation as well as data analysis used are Interactive Model Analysis. Retribution for business services, especially tourist areas, has been running and the regional tourism office through coordination tasks has not been carried out optimally. This can be seen in the achievement of the target for retribution for the tourist area of ??Tomohon City, which has not yet reached the target.